2023
DOI: 10.1177/00315125231197840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moving Tactile Stimuli to Mimic Altered Weight Distribution During Gait on Quiet Stance Body Sway

Yasushi Sawaguchi,
Taku Kawasaki,
Koichi Hiraoka

Abstract: Our purpose in the present study was to examine whether moving tactile stimuli to the sole to mimic moving weight distribution over the feet during gait would influence body sway in quiet stance. Fifteen healthy males maintained the quiet stance, and we delivered moving tactile stimuli to mimic the change in their weight distribution during gait. Moving tactile stimuli did not change the length of the center of pressure (COP) displacement and COP position. Vision decreased the length of the COP, but it did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We chose only male participants because the therapist in this study was male, and we sought to minimize arousing sexual reactions to pelvic touch in cross-sex patient–therapist interactions. Our sample size was based on sample sizes in previous studies that found a significant effect of vision or tactile sensation on body sway during a quiet stance [ 12 ] ( n = 16) and found a significant difference in the reproduction of active and passive movements [ 8 ] ( n = 16). According to the number of the participants in those previous studies, we considered that 16 participants were sufficient to detect the significant difference in the reproduction error of the active and passive pelvis movement instructions in stance.…”
Section: Methodsmentioning
confidence: 99%
“…We chose only male participants because the therapist in this study was male, and we sought to minimize arousing sexual reactions to pelvic touch in cross-sex patient–therapist interactions. Our sample size was based on sample sizes in previous studies that found a significant effect of vision or tactile sensation on body sway during a quiet stance [ 12 ] ( n = 16) and found a significant difference in the reproduction of active and passive movements [ 8 ] ( n = 16). According to the number of the participants in those previous studies, we considered that 16 participants were sufficient to detect the significant difference in the reproduction error of the active and passive pelvis movement instructions in stance.…”
Section: Methodsmentioning
confidence: 99%